Pemikiran Ibnu Khaldun tentang Fondasi Awal Kajian Sosiologi dalam Tradisi Keilmuan Islam - Siti Ami Najmiyyah; Nurlela; Ajudin Wahid; Eva Nurziah (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2024)
This study aims to analyze conceptually and historically Ibn Khaldun’s contributions to the development of sociology within the Islamic intellectual tradition, particularly through his seminal work Muqaddimah. Employing a qualitative approach with library research methods, this study examines key sociological concepts formulated by Ibn Khaldun, including ‘ashabiyah (social cohesion), ‘umr?n (civilization), and the cyclical theory of the rise and decline of societies and states. Unlike conventional historical narratives, Ibn Khaldun developed a systematic analytical framework that integrates social, political, economic, and cultural dimensions of human civilization. The novelty of this research lies in positioning Ibn Khaldun’s thought as a foundational paradigm for contemporary Islamic sociology, offering an alternative to Western-centric sociological theories by grounding social analysis in Islamic epistemology and ethical values. The findings demonstrate that Ibn Khaldun’s sociological framework remains relevant for addressing modern social dynamics and contributes significantly to the formulation of an integrative, value-based, and context-sensitive sociological discourse within Islamic scholarship.